Is efficiency a viable criterion for sub-maximal vertical jumping? - Vanrenterghem, J.; Bobbert, M.; Casius, R.; de Clercq, D. (ISB Congress, 2006)
For the execution of a maximal vertical jump from stance, humans show a unique movement pattern. Over the past decades, researchers have tried to identify the criterion that generates the control signals for this. Through simulation studies it has been shown that a unique movement pattern most likely generates the maximal height achieved by the musculo-skeletal system [1]. In a recent study the authors found that for jumps towards a sub-maximal target height, humans also have stereotyped movement patterns across individuals [2]. These mainly consisted of decreasing countermovement amplitude for decreasing target heights. According to [2], this indicated that humans could minimize energy-consumption for a sub-maximal jump. Another possibility is that humans simply minimize the total duration of the jump. The purpose of this study was to test the hypothesis that one of these criteria causes the stereotype adaptations for sub-maximal jumping in humans. For this purpose, sub-maximal vertical jumps of a simulation model were generated and the movement patterns were compared with movement patterns observed in humans.